2016
DOI: 10.1016/j.crvi.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Expressing the sweet potato orange gene in transgenic potato improves drought tolerance and marketable tuber production

Abstract: Potato (Solanum tuberosum L.) is generally considered to be sensitive to drought stress. Even short periods of water shortage can result in reduced tuber production and quality. We previously reported that transgenic potato plants expressing the sweet potato orange gene (IbOr) under the control of the stress-inducible SWPA2 promoter (referred to as SOR plants) showed increased tolerance to methyl viologen-mediated oxidative stress and high salinity, along with increased carotenoid contents. In this study, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…These findings suggest that Or is a multi-functional protein. Interestingly, recent work showed that transgenic sweetpotato calli, Arabidopsis , alfalfa, and potato overexpressing IbOr accumulate carotenoids and maintain higher photosystem II (PSII) efficiency and chlorophyll content under abiotic stress (Kim et al, 2013; Park et al, 2015, 2016; Wang et al, 2015; Cho et al, 2016). However, the mechanisms underlying the effects of Or on carotenoid biosynthesis and the abiotic stress response are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that Or is a multi-functional protein. Interestingly, recent work showed that transgenic sweetpotato calli, Arabidopsis , alfalfa, and potato overexpressing IbOr accumulate carotenoids and maintain higher photosystem II (PSII) efficiency and chlorophyll content under abiotic stress (Kim et al, 2013; Park et al, 2015, 2016; Wang et al, 2015; Cho et al, 2016). However, the mechanisms underlying the effects of Or on carotenoid biosynthesis and the abiotic stress response are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Expression levels of some genes encoding for plant DnaJ which are targeted to the chloroplast are induced by different abiotic stresses [38][39][40] . In addition, in sweet potato Or expression was differentially affected by salt, drought, oxidative stress and heat stress, depending on the analyzed tissue 10,[41][42][43] . In sweet potato, Or was downregulated by heat stress in leaves, as the case of CsOr-a and CsOr-b in heat-treated stigmas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, transgenic alfalfa and potato plants overexpressing IbOr were generated and characterized (Cho et al 2016, Goo et al 2015, Wang et al 2015). Transgenic alfalfa and potato plants exhibit elevated tolerance to various abiotic stresses including oxidative, salt and drought stress, as well as higher carotenoid content (Goo et al 2015, Wang et al 2015).…”
Section: Accumulation Of Carotenoids By Ibor Genementioning
confidence: 99%